2023
DOI: 10.1002/ptr.7907
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol alleviates pulmonary fibrosis inchronic obstructive pulmonary disease by targeting transient receptor potential vanilloid 4‐ankyrin repeat domain

Abstract: Transient receptor potential vanilloid 4 (TRPV4) plays a role in regulating pulmonary fibrosis (PF). While several TRPV4 antagonists including magnolol (MAG), have been discovered, the mechanism of action is not fully understood. This study aimed to investigate the effect of MAG on alleviating fibrosis in chronic obstructive pulmonary disease (COPD) based on TRPV4, and to further analyze its mechanism of action on TRPV4. COPD was induced using cigarette smoke and LPS. The therapeutic effect of MAG on COPD‐indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…High concentrations of KCl have been commonly used to study smooth muscle contraction elicited by membrane depolarization. We observed that incubation of tracheal tissues with 100 nM GSK219 decreased smooth muscle contraction induced by increasing KCl concentrations (10,20,40,80,120, and 160 mM) (Figure 9).…”
Section: Trpv4 Blockade Also Lowers Smooth Muscle Reactivity To Kclmentioning
confidence: 85%
See 3 more Smart Citations
“…High concentrations of KCl have been commonly used to study smooth muscle contraction elicited by membrane depolarization. We observed that incubation of tracheal tissues with 100 nM GSK219 decreased smooth muscle contraction induced by increasing KCl concentrations (10,20,40,80,120, and 160 mM) (Figure 9).…”
Section: Trpv4 Blockade Also Lowers Smooth Muscle Reactivity To Kclmentioning
confidence: 85%
“…High concentrations of KCl have been commonly used to study smooth muscle contraction elicited by membrane depolarization. We observed that incubation of tracheal tissues with 100 nM GSK219 decreased smooth muscle contraction induced by increasing KCl concentrations (10,20,40,80,120, and 160 mM) (Figure 9). Since KCl-induced contraction of guinea pig ASM is entirely dependent on membrane depolarization and hence external Ca 2+ entry through L-VDCCs activation [40,61], we conducted patch-clamp experiments to rule out the possibility that GSK219 might block this channel.…”
Section: Trpv4 Blockade Also Lowers Smooth Muscle Reactivity To Kclmentioning
confidence: 85%
See 2 more Smart Citations